Comprehensive mechanical & metabolic imaging of abdominal aortic aneurysm with 4D flow/ FDG PET on an integrated PETMRI: a feasibility study. (20th July 2021) - Wan, S; Steeden, J; Rega, M; Hoy, L; Walls, D; Endozo, R; Hoath, J; Shortman, R; Agu, O; Menezes, L; Muthurangu, V; Groves, AM
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): NIHR Biomedical Research Centre, University College London Hospitals. Background: A number of non-invasive imaging derived parameters have been implicated in the development and progression of abdominal aortic aneurysm, although the mechanism, and relationships of many of these are yet to be precisely determined.  Mechanical parameters can now be studied using 4D phase contrast magnetic resonance (PCMR), and inflammatory cellular activity can be detected with FDG PET. Purpose: It may be postulated that inflammation of the aortic wall may be the intermediary at the tissue level linking mechanical wall shear stress (WSS) to aneurysm progression. It may be feasible to study 4D PCMR and FDG PET at the same patient visit on a PETMRI platform, with the potential to enhance temporal and spatial co-registration and improving the understanding of any relationship between these two parameters.  Our study aims to assess feasibility of studying these on an integrated PETMRI system. Methods: 7 patients with known aortic aneurysm were recruited in a vascular ultrasound screening follow up clinic.  During a single visit following 6 hours fasting, all patients underwent FDG injection and 60 minutes uptake period.  With quiet breathing, list mode PET acquisition and concurrent 4D PCMR was acquired using stacks of spiral acquisition, with ECG trace information for retrospective gating.  Images from the 4D PCMR and FDG PET were assessed qualitatively for image quality and visual matching. Results: All 7 patients completed the study.  Overall image quality was adequate to good.  There is qualitatively a good concordance with impression of positive correlation between wall shear stress and inflammatory signal (see attached image). Conclusion: We have demonstrated feasibility of combined assessment of mechanical and metabolic imaging parameters using an integrated PETMRI system.  Initial findings show there to be a broad concordance of wall shear stress and inflammatory signal in the abdominal aneurysm.